Data protection and space : What challenges will the General Data Protection Regulation face when dealing with space-based data? - Bu-Pasha, Shakila; Kuusniemi, Heidi (Henry Stewart Publications, 2021)
Recently, space or satellite technology, as well as space data applications, is developing rapidly, resulting in a variety of uses. At the same time, related legal issues raise questions about how they can be handled efficiently. In addition to pointing out the importance of managing satellite activities in a legally sound environment, this paper explains the relevance of the General Data Protection Regulation and the challenges it will face in handling space-based data, as well as in managing threats to privacy and personal data regarding the outer space context.
Keywords: GDPR; satellite; space-based data; technology; personal data; privacy